Solomon Islands Teachers : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2015)
This report presents results of the application of the SABER-teachers tool in Solomon Islands. It describes the performance of Solomon Islands’ education system in achieving each of the eight teacher policy goals, alongside comparative information from education systems that have consistently scored highly on international student achievement tests and have participated in the SABER-Teachers initiative. Additional detailed descriptive information on the teacher policies of the education systems of Solomon Islands and other countries can be found on the SABER-teachers website.